Drivers of Green Purchase Behavior Among Female Gen Z in Jabodetabek, Indonesia: The Roles of Eco-Labeling, Green Brand Image, Environmental Marketing, and Sustainability Influencers - Kuspuji Catur Bagus Wicaksono (Inkubis : Jurnal Ekonomi dan Bisnis, 2026)
Background: Jabodetabek, Indonesia's largest metropolitan area, faces critical environmental challenges alongside rapid digital adoption among Generation Z. Objective: This study investigates determinants of green purchase behavior among 220 female Gen Z consumers (aged 18-25) using an extended Theory of Planned Behavior framework. Methods: Employing PLS-SEM via SmartPLS 4.0, data were collected from 220 female Gen Z respondents (aged 18-25) in Jabodetabek using stratified sampling across five constituent areas. Female Gen Z was selected as the focal demographic due to their disproportionate influence on household purchasing decisions and higher engagement with sustainability discourses in urban Indonesia. The study analyzes the effects of eco-labeling, green brand image, environmental marketing, and sustainability influencers on green purchase behavior. Results: Results show all four constructs significantly predict green purchase behavior (p < 0.001), with eco-labeling demonstrating the strongest effect (β = 0.352, p < 0.001), followed by sustainability influencers (β = 0.342), environmental marketing (β = 0.341), and green brand image (β = 0.328). The model explains 64.3% of variance in green purchase behavior (R2 = 0.643, Q2 = 0.412). Eco-labeling exhibits the largest effect size (f2 = 0.142), followed by sustainability influencers (f2 = 0.138). The moderation effect of sustainability influencers on the environmental marketing-green purchase behavior relationship is also significant (beta = 0.118, p < 0.01). Model fit indices indicate acceptable fit (SRMR = 0.062). Conclusion: These findings provide context-specific insights for policymakers and marketers in urban Indonesia to leverage eco-certifications and sustainability influencers for promoting sustainable consumption.